2015
DOI: 10.1111/jgh.12777
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease in patients with diabetes: Preliminary study

Abstract: Background and Aim: Some studies report that complications of gastroesophageal reflux disease (GERD) occur more frequently in patients with diabetes mellitus (DM) than in non-diabetic patients. This study used transnasal endoscopy to elucidate the current status of concurrent GERD in patients with type 2 diabetes mellitus, and to examine the associations between intraesophageal pressure and GERD, as well as other neuropathic conditions. Methods: The study included 57 outpatients with type 2 diabetes mellitus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Also, Zhang et al (11) GERD is more prevalent in females than males. In contrast, Sakitani et al (12) and Fujiwara et al (13) showed that both sexes reported more cases of endoscopic GERD in males than females.…”
Section: Discussionmentioning
confidence: 92%
“…Also, Zhang et al (11) GERD is more prevalent in females than males. In contrast, Sakitani et al (12) and Fujiwara et al (13) showed that both sexes reported more cases of endoscopic GERD in males than females.…”
Section: Discussionmentioning
confidence: 92%
“…There was also a significant relationship between GERD and gender, showing that the complicated form of GERD was more frequent in men. However, there are no significant associations between the presence of reflux disease and other diabetic complications [21].…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 98%
“…Some studies indicate that gastroesophageal reflux disease (GERD) is more common in diabetic patients than in non-diabetics [19][20][21].…”
Section: Gastroesophageal Reflux Diseasementioning
confidence: 99%
See 1 more Smart Citation